Prevalence and distribution of human papillomavirus in genital warts in Can Tho City, Vietnam: a cross-sectional study - Lac Thi Kim Ngan; Huynh Van Ba; Dao Hoang Thien Kim; Dang Tran Dang Khoa; Nguyen Tan Hung; Pham Thi Bao Tram; Nguyen Thi Thuy Trang; Nguyen Hoang Khiem; Pham Thanh Thao; Truong Dieu Hien; Le Van Dat; Hung Do Tran; et al. (Infectious Agents and Cancer)
Abstract Background Human papillomavirus (HPV) is the major causative agent of genital warts and various anogenital cancers. In Vietnam, limited data exists on HPV genotype prevalence and distribution. This study aimed to determine the prevalence and distribution of HPV types among patients with genital warts in Can Tho City and to explore their associations with demographic and clinical characteristics. Methods A cross-sectional study was conducted at Can Tho Dermatology Hospital with 109 patients diagnosed with genital warts. HPV genotyping was performed using real-time PCR and reverse dot blot hybridization to detect both the low- and high-risk HPV types. Associations between HPV types and variables such as age, sex, and lesion site were analyzed statistically. Results HPV was detected in 89% of the patients. The low-risk types HPV11 (50.5%) and HPV6 (47.4%) were the most common. The high-risk types, HPV51 (30.9%) and HPV52 (20.6%), were frequent, especially in females (83.6% vs. 63.3% in males, p = 0.030). Co-infections occurred in 71.6% of females and 60% of males. Lesion location correlated with HPV type distribution. Conclusions The high prevalence of both low- and high-risk HPV types highlights the need for enhanced vaccination coverage and continued HPV surveillance. These findings provide critical data for developing HPV prevention strategies in Vietnam.